2009
DOI: 10.1021/jp809104t
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Controlled Anatase Titanium(IV) Oxide Particles Prepared by Hydrothermal Treatment of Peroxo Titanic Acid in the Presence of Polyvinyl Alcohol

Abstract: Anatase titanium(IV) oxide (TiO2) particles with specific exposed crystal faces were prepared by hydrothermal treatment of peroxo titanic acid (PTA) solution with polyvinyl alcohol as a shape-control reagent. Crystal phase, shape, and size of TiO2 particles were found to be greatly dependent on pH value of PTA solution and time of hydrothermal treatment. TiO2 particles prepared from PTA solution of pH 7 had {101} and {001} exposed crystal faces, and the shape of TiO2 particles changed with the time of hydrothe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
228
1
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 292 publications
(245 citation statements)
references
References 44 publications
12
228
1
4
Order By: Relevance
“…This finding may be helpful to interpret some important photocatalytic processes. For example, a large surface area of {101} facets was suitable for acetaldehyde decomposition, while anatase TiO 2 samples with dominant {001} facets had excellent ability to remove NO and toluene through photocatalytic reactions [94,107].…”
Section: Recent Controversial Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding may be helpful to interpret some important photocatalytic processes. For example, a large surface area of {101} facets was suitable for acetaldehyde decomposition, while anatase TiO 2 samples with dominant {001} facets had excellent ability to remove NO and toluene through photocatalytic reactions [94,107].…”
Section: Recent Controversial Resultsmentioning
confidence: 99%
“…Therefore, an ideal spatial separation of red-ox sites on the anatase particles, with a consequent reduction of electron-hole pairs recombination rate and a parallel photocatalytic efficiency enhancement, may occur [106,107]. This is another crucial aspect concerning potential positive effects induced in photocatalysis by specific TiO 2 crystal engineering.…”
Section: Selective Charge Separationmentioning
confidence: 99%
“…This approach involves the application of fluorinecontaining species (e.g., hydrogen fluoride, ammonium fluoride, titanium(IV) fluoride and tetrafluoroborate ion) as morphology-controlling agents to prevent the formation of more thermodynamically stable octahedral anatase titania particles (OAPs) exposing only {101} facets [22][23][24][25][26][27][28][29][30][31][32][33]. Other compounds including polyvinyl alcohol [34,35] and carbonate ions generated during decomposition of urea have also been used to control the shape [20].…”
Section: Introductionmentioning
confidence: 99%
“…However, the disadvantage of this approach is strong adsorption of shape-control reagents (e.g., fluoride ions) on the crystal surface or their doping into the lattice, which may result in a decrease in photocatalytic activity [34]. Furthermore, at high temperatures, fluorine compounds generate toxic and corrosive products, making scaling-up of the preparation process difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Similar phenomena were also reported in other references [27][28][29] . However, some references observed higher photocatalytic oxidation activity of organics on anatase nanocrystals with well-faceted {101} surfaces than that of the above-mentioned {001} facet [30][31][32] . Farneth et al 21 concluded that the fine Ag particles are mostly deposited by reduction of Ag þ on the {110} face of TiO 2 , while Hotsenpiller et al 22 reached the conclusion that the Ag particles were photocatalytically deposited at higher velocities on the {001} and {011} facets than on the {110} and {010} facets.…”
mentioning
confidence: 98%